Well-Being, Life Satisfaction and Effectiveness among Sapanggar Island Communities: A Perspective of Island Community - Chua, Bee Seok; Getrude Cosmas; Saidatul Nornis Hj. Mahali (2018)
This study is aimed at understanding the index of well-being, satisfaction and effectiveness of community living in Sapanggar Island. It also seeks to examine the differences of the variables based on demographic factors such as gender, generation/age and marital status of study respondents. A total of 124 Sapanggar Island residents were selected randomly and involved in this study. The WHO-5 Wellness Index, The Satisfaction with Life Scale (SWLS) and The Life Effectiveness Questionnaire are used to measure the variables in this study. The findings indicate that the index of well-being and satisfaction of the community in Sapanggar Island is at medium and high levels while the level of effectiveness reported is high in all dimensions except for emotional control. For emotional control dimensions, many of the respondents reported having low capability compared to other dimensions of life effectiveness. The findings also reported that female respondents were more satisfied with their lives on Sapanggar Island compared to male respondents. In terms of wellness index, reports provided are not different according to gender, generation/age or the respondents’ marital status. In terms of life effectiveness, it was found that age and marital status influenced how these respondents perceived their capabilities, especially for time management dimensions, intelligence flexibility, active leadership and active initiative, whereas married and older respondents (generation X) demonstrated higher ability.